An Adrenal Hepatoid Adenocarcinoma with Left Renal Vein Thrombosis Extending into the Inferior Vena Cava - Deng, Xiaokai; Jin, Yuting; Yang, Wenxue; Wang, Shuaibin; Mu, Haiqi; Yu, Kaiyuan; He, Youhua (Urology Journal, 2019)
Hepatoid adenocarcinoma (HAC) is an uncommon tumor with morphological resemblance to hepatocellular carcinoma. HAC of the adrenal glands is extremely rare. Here, we report the case of an 83-year-old man with adrenal HAC who presented with a greatly increased preoperative serum alpha-fetoprotein level (> 24,200 ng/mL). The findings of magnetic resonance imaging and contrast-enhanced abdominal computed tomography revealed a large mass occupying the left adrenal gland region as well as thrombosis of the renal vein extending into the inferior vena cava. Subsequently, the adrenal HAC was treated by surgical resection and targeted sorafenib therapy. However, the patient died 9 months later because of systemic metastasis of the tumor. In conclusion, adrenal HAC with inferior vena cava tumor thrombosis is extremely rare and challenging to diagnose and treat. Pathological and immunohistochemical examination are helpful for diagnosis and surgical excision is the main strategy for treating the tumor.